The Experimental Determination of Interfacial Energies for Solid Cd in Equilibrium with Sn-Cd-Sb Liquid - Ozturk, Esra; Aksoz, Sezen; Keslioglu, Kazim; Marasli, Necmettin (SPRINGER, 2014)
The equilibrated grain boundary groove shapes of solid Cd in equilibrium with Sn-Cd-Sb liquid were observed from a quenched sample by using a radial heat flow apparatus. The Gibbs-Thomson coefficient, solid-liquid interfacial energy, and grain boundary energy of the solid Cd were determined from the observed grain boundary groove shapes. The thermal conductivity of the eutectic solid phase for Sn-35.80 at. pct Cd-6.71 at. pct Sb alloy and the thermal conductivity ratio of the liquid phase to the solid phase for Sn-35.80 at. pct Cd-6.71 at. pct Sb alloy at eutectic temperature were also measured with a radial heat flow apparatus and a Bridgman-type growth apparatus, respectively.
Keywords: SURFACE ENERGIES; AL-CU; SYSTEM; METALS; ALLOY; WATER; MELT; ICE; Materials Science; Metallurgy & Metallurgical Engineering